Representaciones sociales de ley, justicia e injusticia: Un estudio con jóvenes argentinos y brasileńos utilizando la técnica de evocación libre de palabras - De Morais Shimizu, Alessandra [UNESP]; De Stefano Menin, María Suzana [UNESP] (My University, 2004)
This study aims to analyze the main social representations of law, justice and injustice presented by Argentinean and Brazilian youngsters. The Brazilian group consisted of 621 polled of three different regions - Floriano / PI, Erechim / RS, and Marília / SP. From Argentina, 200 youngsters of Avellaneda city (Buenos Aires metropolitan region) participated. All the samples were proportionally divided according to die kind of school (public or private) and the school year attended (8th grade and 11th grade, considering the equivalent grade in Argentina). The data collection technique consisted of semi directed questionnaire composed by the free evocation of words technique. The procedure used to evaluate the results Was the Analysis Correspondence Method (ANACOR). The results demonstrate important variations related to the youngsters' nationality and they were discussed so that the presented representations were contextualized.
Social representations of law, justice and injustice: A study with Argentinean and Brazilian adolescents
Keywords: Free evocation of words; Law-justice-injustice; Social representations theory